The first 1000 days of life, an opportunity that must be taken for the future generations - Hamid Jan Jan Mohamed (World Nutrition Journal, 2022)
The â€œdevelopmental origins of health and diseaseâ€ (DOHaD) is a concept that has proven the link between the state of maternal health and risk from disease in later childhood and adult life with the environmental conditions of the early life. Hence, the first 1000 days is reported as a critical period of opportunity for interventions to prevent stunting and other associated pathologies at later life.